2015
DOI: 10.1051/0004-6361/201527391
|View full text |Cite
|
Sign up to set email alerts
|

Carbon and nitrogen abundances of individual stars in the Sculptor dwarf spheroidal galaxy

Abstract: We present [C/Fe] and [N/Fe] abundance ratios and CH(λ4300) and S(λ3883) index measurements for 94 red giant branch (RGB) stars in the Sculptor dwarf spheroidal galaxy from VLT/VIMOS MOS observations at a resolving power R = 1150 at 4020 Å. This is the first time that [N/Fe] abundances are derived for a large number of stars in a dwarf spheroidal. We found a trend for the [C/Fe] abundance to decrease with increasing luminosity on the RGB across the whole metallicity range, a phenomenon observed in both fiel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 93 publications
5
30
2
Order By: Relevance
“…Here, the blue and red histograms represent the findings from methods I and III, respectively. For comparison, we indicate the fractions for bound cluster stars as reported by Carretta et al (2009, solid dence for CN-bimodalities amongst the dSph field star populations is sparse (e.g., Smith & Dopita 1983;Lardo et al 2016a;Norris et al 2017;Salgado et al 2019). However, several GCs in the MW have been associated with dwarf-accretion events.…”
Section: The Fraction Of Chemically Altered Stars Amongst Bona-fide Ementioning
confidence: 73%
“…Here, the blue and red histograms represent the findings from methods I and III, respectively. For comparison, we indicate the fractions for bound cluster stars as reported by Carretta et al (2009, solid dence for CN-bimodalities amongst the dSph field star populations is sparse (e.g., Smith & Dopita 1983;Lardo et al 2016a;Norris et al 2017;Salgado et al 2019). However, several GCs in the MW have been associated with dwarf-accretion events.…”
Section: The Fraction Of Chemically Altered Stars Amongst Bona-fide Ementioning
confidence: 73%
“…If such stars exist, it would favour a picture in which massive GCs did form, but were subsequently destroyed. So far, no significant populations of field stars with GC-like abundance patterns have been found in dwarf galaxies (Lemasle et al 2014;Lardo et al 2016;Suda et al 2017), but the samples may still be too small to rule out an enriched fraction of a few percent, similar to that seen in the Milky Way halo (Martell et al 2011(Martell et al , 2016. …”
Section: Metallicitiesmentioning
confidence: 96%
“…Prior to this study, only four CEMP stars had been identified in Sculptor (Skúladóttir et al 2015b;Lardo et al 2016;Salgado et al 2016). Of those, only one was a CEMP-no star, resulting in an apparent disagreement between the CEMP fraction of Sculptor and the CEMP fraction of the Milky Way halo (∼42%).…”
Section: Discussionmentioning
confidence: 99%
“…Given Kirby et al (2015), 94 medium-resolution measurements from Lardo et al (2016), and 28 stars with high-resolution measurements Geisler et al 2005;Frebel et al 2010a;Tafelmeyer et al 2010;Kirby & Cohen 2012;Starkenburg et al 2013;Jablonka et al 2015;Simon et al 2015;Skúladóttir et al 2015b). Thirteen of these stars have [Fe/H] < −2.8, one of which is potentially a CEMP-no star (Scl 11_1_4296 in Simon et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation